On some generalized integral inequalities for φ-convex functions - SARİKAYA, Mehmet Zeki and BÜYÜKEKEN, Meltem and KIRIS, Mehmet Eyüp (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
The main goal of the paper is to state and prove some new general inequalities for φ-convex function. Mathematics Subject Classification (2010): 26D15, 41A55, 26D10.